Small T Oncoprotein of Merkel Cell Polyomavirus Attenuates Cisplatin-Induced Apoptosis and Enhances E1, E6/E7, MMP-1, and Ki-67 Expression in HeLa Cervical Cancer Cells - Fatemeh Pakdel; Seyed Masoud Hosseini; Neda Soleimani; Ali Farhadi (Advanced Pharmaceutical Bulletin, 2025)
Purpose: Cervical cancer (CxCa) is primarily caused by high-risk human papillomaviruses (hrHPV), which disrupt p53 and pRb regulation, leading to uncontrolled growth and progression. Co-infection with polyomaviruses like MCPyV in some HPV-positive cases suggests a potential combined effect on tumor development. Cisplatin is commonly used for advanced CxCa, but resistance remains a challenge. This study examines whether MCPyV sT oncoprotein and HPV-18 oncoproteins affect key gene transcription, influencing proliferation and cisplatin resistance in CxCa. Methods: The sT gene was cloned into the pCMV6 vector, and HeLa cells were transfected with pCMV6-sT using Lipofectamine 3000. Transfection efficiency was assessed via fluorescence microscopy and flow cytometry. Protein expression was analyzed using SDS-PAGE and Western blotting. Cytotoxicity was measured with the MTT assay, gene expression was analyzed by RT-qPCR, Ki-67 staining was performed on cell blocks, and cisplatin-induced effects on proliferation and apoptosis were examined. Results: Cytotoxicity assays showed a significant increase in cell viability at 0.2 μg of sT plasmid after 72 hours (13.76%, P<0.05). MCPyV sT expression significantly upregulated E1 (4.22-fold), E6/E7 (3.80-fold), and MMP1 (6-fold) mRNA levels (P<0.001). Increased Ki-67 positivity indicated enhanced proliferation. Additionally, sT expression reduced cisplatin-induced apoptosis, with fewer apoptotic cells observed in the sT+cisplatin group than in the cisplatin-only group (25.9% vs. 38.3%, P<0.05). Conclusion: The presence of MCPyV sT and HPV oncoproteins together enhances resistance to cisplatin-induced apoptosis in CxCa cells, highlighting the need for further investigation into viral oncoprotein interactions to overcome therapeutic resistance.